Original paperThe dosimetric impact of vaginal balloon-packing on intracavitary high-dose-rate brachytherapy for gynecological cancer - Rockey, William M.; Bhatia, Sudershan K.; Jacobson, Geraldine M.; Kim, Yusung (Journal of Contemporary Brachytherapy, 2013)
Purpose : We perform a clinical retrospective study to determine whether a vaginal balloon-packing system provides a dosimetric reduction to organs at risk (OARs) versus traditional gauze packing for gynecological high-dose-rate brachytherapy (HDR-BT). We also test various balloon filling materials for optimizing imaging quality. Material and methods: Filling materials for balloon-packing were evaluated based on imaging quality with X-ray, computerized tomography, and magnetic resonance imaging modalities. We then retrospectively reviewed 45 HDR-BT plans of 18 patients performed with gauze packing and 39 plans of 16 patients performed with balloon-packing. Twelve patients received both gauze and balloon-packing. HDR-BT was delivered with an iridium-192 afterloader and a Fletcher-Suit-Declos-style T&O applicator. At each fraction, 3D imaging was obtained. The D2 cc values of OARs were calculated, as well as ICRU-defined point doses. Results: I n the 84 HDR fractions reviewed, vaginal balloon-packing provides statistically equivalent doses to rectum, bladder, and sigmoid compared to gauze packing. On average balloon-packing produced average reductions of 3.3% and 6.9% in the rectal and sigmoid D2 cc doses and an increase of 3.2% to the bladder D2 cc dose (normalized to prescription dose), although none of these values were statistically significant for the twelve patients who received both gauze and balloon-packing (32 and 40 total fractions, respectively). Conclusions : In the 84 HDR fractions analyzed, vaginal balloon-packing is as effective as gauze packing for dose sparing to the rectum, bladder, and sigmoid. A 1 : 1 solution of saline and contrast for filling material enables easy contouring for image-guided HDR with minimal artefacts.